2007
DOI: 10.1044/1092-4388(2007/085)
|View full text |Cite
|
Sign up to set email alerts
|

Imitative Production of Rising Speech Intonation in Pediatric Cochlear Implant Recipients

Abstract: Purpose-This study investigated the acoustic characteristics of pediatric cochlear implant (CI) recipients' imitative production of rising speech intonation, in relation to the perceptual judgments by listeners with normal hearing (NH).Method-Recordings of a yes-no interrogative utterance imitated by 24 prelingually deafened children with a CI were extracted from annual evaluation sessions. These utterances were perceptually judged by adult NH listeners in regard with intonation contour type (non-rise, partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 41 publications
3
32
0
Order By: Relevance
“…Furthermore, CI children demonstrate difficulty with perceiving more subtle emotions such as disappointment and surprise (Nakata, et al, 2012). Speech production studies suggest a lack of appropriate pitch contour in conveying questions and/or statements in CI children (Peng, et al, 2008; Peng, et al, 2007; Chin, et al, 2012). Recent preliminary data from Chatterjee et al (2016) illustrates that CI children’s productions of emotional speech incorporate smaller contrasts between happy and sad speech in mean pitch, pitch range, intensity, and spectral centroid compared to NH children.…”
Section: Review Of Prosody and Voice Emotion Studies In Cochlear Imentioning
confidence: 99%
“…Furthermore, CI children demonstrate difficulty with perceiving more subtle emotions such as disappointment and surprise (Nakata, et al, 2012). Speech production studies suggest a lack of appropriate pitch contour in conveying questions and/or statements in CI children (Peng, et al, 2008; Peng, et al, 2007; Chin, et al, 2012). Recent preliminary data from Chatterjee et al (2016) illustrates that CI children’s productions of emotional speech incorporate smaller contrasts between happy and sad speech in mean pitch, pitch range, intensity, and spectral centroid compared to NH children.…”
Section: Review Of Prosody and Voice Emotion Studies In Cochlear Imentioning
confidence: 99%
“…In particular, f 0 tends to be weakly represented in CIs (Peng, Tomblin, Spencer, & Hurtig, 2007; Kuo, Rosen, & Faulkner, 2008). To investigate the limited representation of f 0 in CIs, Lin, Lee, Huang, & Peng (2007) asked adult Mandarin speakers with NH to identify tones in monosyllabic word productions that acoustically simulated CIs with a different number of channels.…”
mentioning
confidence: 99%
“…In Cantonese, for example, a group of 3 children acquired lexical pitch patterns corresponding to the tonal inventory more slowly than they acquired the vowel inventory (Barry, Blamey, Lee, & Cheung, 2000), suggesting that f 0 patterns may be more difficult to acquire than speech sounds. In studies of intonation production, Peng, Tomblin, Spencer, & Hurtig (2007) elicited imitated productions of a rising contour ( yes-no question) from children with a CI. According to the judgments of adults with NH, the children with a CI did not produce the contour accurately.…”
mentioning
confidence: 99%
“…Also, the duration of CI use after late implantation showed no significant influence in these CI users, although one might expect an influence as described by Peng et al [48]. Tanamati et al [49] showed that children with postlingual deafness can achieve high scores of intelligibility: after 10 years of CI use, 8 children received the highest scores and only 2 children received low scores.…”
Section: Discussionmentioning
confidence: 83%